Visible / infrared wide-spectrum high-absorption transition metal-based high-entropy alloy material as well as preparation method and application thereof

By preparing a transition metal-based high-entropy alloy coating, the problems of narrow spectral absorption range and high-temperature stability of existing ultra-black coatings are solved, full-spectrum high absorption and high-temperature oxidation resistance are achieved, and the signal-to-noise ratio of deep space detectors is improved.

CN120624916APending Publication Date: 2025-09-12HARBIN INST OF TECH +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510766617.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-10
Publication Date
2025-09-12

AI Technical Summary

Technical Problem

Existing ultra-black coatings have a narrow spectral absorption range in deep space exploration, making it difficult to maintain high absorption rates in the entire visible-infrared band. They are also prone to oxidation or agglomeration and failure in high-temperature environments, and cannot meet the adaptability requirements of deep space probes to extreme environments.

Method used

Transition metal-based high-entropy alloy materials are used to prepare nanocrystalline high-entropy alloy powders through high-energy ball milling to form a single-phase BCC solid solution structure. The powders are then mixed with polyurethane resin and scraped onto a substrate to prepare a coating that achieves high absorption across the entire spectrum.

Benefits of technology

It achieves a high absorption rate of over 86% in the full spectral range of 0.2-16 μm, has excellent high-temperature oxidation resistance and mechanical stability, and improves the signal-to-noise ratio of deep space detectors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120624916A_ABST
    Figure CN120624916A_ABST
Patent Text Reader

Abstract

The invention discloses a visible / infrared wide-spectrum high-absorption transition metal-based high-entropy alloy material and a preparation method and application thereof, and belongs to the technical field of functional materials and preparation thereof. The problems that an existing ultra-black coating is low in intrinsic light absorption performance and narrow in spectrum coverage range are solved. Transition metal Al, Cr, Cu, Ni and Nb elements are adopted as a five-element high-entropy alloy system, formation of intermetallic compounds is inhibited to the maximum extent through configuration entropy, and nanocrystalline high-entropy alloy powder of a stable single-phase BCC solid solution structure with remarkable lattice distortion is prepared through a high-energy ball milling technology. And through a stepped energy level structure formed through orbit hybridization of multiple transition metal elements d, continuous state density distribution is constructed near the Fermi level, electron transition is promoted to cover the full wave band from ultraviolet to far infrared, and the absorption rate breakthrough of 86% or above is achieved within the full spectrum range of 0.2-16 microns.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a visible / infrared wide spectrum high-absorption transition metal-based high-entropy alloy material and a preparation method and application thereof, belonging to the technical field of functional materials and their preparation. Background Art

[0002] In deep space exploration missions, space optical systems need to achieve high-sensitivity capture of weak signals in extreme environments, which poses unprecedented challenges to stray light suppression technology. Stray radiation sources in the deep space background, such as solar scattering, interstellar dust reflection, and internal thermal radiation of the system, can easily form multiple scattering or reflections on the surface of optical components, causing a sharp drop in the detector's signal-to-noise ratio and even masking the target signal. Although traditional mechanical structures such as sunshades and light-blocking rings can partially suppress external stray light, they are unable to cope with the spontaneous radiation interference caused by complex surfaces, ultra-large fields of view, and low-temperature deformation of materials. In this context, ultra-black coatings, with their wide-spectrum high absorption characteristics in the visible and infrared spectral ranges, have become the core means to break through technical bottlenecks.

[0003] Ultra-black coatings, by eliminating stray light interference and improving the signal-to-noise ratio of optical systems, play an irreplaceable role in deep space exploration. Currently, ultra-black coatings used in deep space exploration equipment primarily consist of carbon-based composites and metal-based coatings. However, these materials have significant limitations. For example, carbon-based materials are susceptible to oxidative decomposition at high temperatures, leading to structural collapse of the coating. Metal-based materials, such as nanoparticles (Au, Ag, etc.), rely on localized surface plasmon resonance (LSPR), resulting in extremely narrow absorption peaks and low absorptivity across a wide spectral range. They are also prone to aggregation and failure at high temperatures. Furthermore, the spectral absorption range of existing coatings is primarily concentrated in the visible-near-infrared (0.4-2 μm) band, with a sharp drop in absorptivity in the ultraviolet (<0.4 μm) and mid- and far-infrared (2-16 μm) bands. This severely limits the full-spectrum capture capability of deep space probes for weak cosmic signals. Therefore, the development of a new ultra-black coating material that combines high absorption across a broad spectral range (0.2-16 μm), high-temperature oxidation resistance, and excellent mechanical stability is urgently needed. The material needs to maintain a high absorption rate in the entire visible-infrared band and have excellent stability to meet the urgent demand for optical devices to adapt to extreme environments in future deep space exploration missions. Summary of the Invention

[0004] In order to solve the problems of low intrinsic light absorption performance and narrow spectral coverage of existing ultra-black coatings, the present invention provides a visible / infrared wide spectrum high absorption transition metal-based high entropy alloy material and its preparation method and application.

[0005] The technical solution of the present invention: One of the objectives of the present invention is to provide a visible / infrared wide spectrum high absorption transition metal-based high entropy alloy material, which includes Al, Cr, Cu, Ni, and Nb elements, and the high entropy alloy material has a single-phase BCC solid solution structure.

[0006] It is further defined that the molar percentage of each component is: Al: 5-35%, Cr: 5-35%, Cu: 5-35%, Ni: 5-35%, Nb: 5-35%.

[0007] It is further defined that the molar percentage of each component is: Al: 25%, Cr: 20%, Cu: 15%, Ni: 25%, Nb: 15%.

[0008] A second object of the present invention is to provide a method for preparing the above-mentioned visible / infrared wide spectrum high absorption transition metal-based high entropy alloy material, which comprises placing the metal particles constituting the high entropy alloy material in a high-energy ball milling tank in a molar ratio, and performing ball milling treatment under argon protection to obtain the high entropy alloy material.

[0009] It is further defined that the ball milling speed is 300-600 rpm, the time is 20-100 h, and the ball-to-material ratio is 10~20:1.

[0010] The third object of the present invention is to provide a visible / infrared wide spectrum high absorption transition metal-based high entropy alloy coating, which comprises the above-mentioned visible / infrared wide spectrum high absorption transition metal-based high entropy alloy material and polyurethane resin.

[0011] It is further defined that the mass ratio of the high entropy alloy material to the polyurethane resin is 1:(1~5).

[0012] It is further defined that the coating thickness is 20-100 μm.

[0013] A fourth object of the present invention is to provide a method for preparing the above-mentioned visible / infrared wide spectrum high absorption transition metal-based high entropy alloy coating, the preparation method comprising: uniformly mixing high entropy alloy powder and polyurethane resin to obtain a composite slurry, using a scraper to evenly apply the composite slurry on a pretreated substrate, performing multiple coatings, and leveling at room temperature after each coating, and standing and curing at room temperature after coating is completed, and curing is completed to obtain a high entropy alloy coating.

[0014] It is further defined that the leveling time at room temperature is 20 minutes.

[0015] It is further defined that the curing time at room temperature is 24 hours.

[0016] A fifth object of the present invention is to provide an application of the above-mentioned visible / infrared wide spectrum high absorption transition metal-based high entropy alloy coating, specifically as an ultra-black coating for protecting optical devices in deep space exploration missions.

[0017] Beneficial effects: The present invention adopts a transition metal-based five-element high-entropy alloy system through multi-principal component collaborative design and high-entropy effect regulation, utilizes configurational entropy maximization to suppress the formation of intermetallic compounds, and prepares nanocrystalline high-entropy alloy powder through a high-energy ball milling process. The severe plastic deformation and cold welding effect generated during the ball milling process promote atomic-level uniform mixing of multiple elements, forming a stable single-phase BCC solid solution structure with significant lattice distortion. The stepped energy level structure formed by the d-orbital hybridization of multiple transition metal elements is used to construct a continuous state density distribution near the Fermi level, promoting electron transitions to cover the entire ultraviolet to far infrared band, and achieving an absorption rate breakthrough of more than 86% in the full spectral range of 0.2-16μm.

[0018] The present invention utilizes the aforementioned high-entropy alloy system to fabricate an ultra-black coating with broad visible / infrared spectrum absorption. The coating utilizes nanoscale particles of a transition-metal-based high-entropy alloy as the ultra-black functional elemental material, and a polyurethane resin as the coating binder. The coating is prepared by doctor blade coating and then applied to an aluminum substrate, resulting in an ultra-black coating with high absorption across the visible / infrared spectrum. Density functional theory (DFT) calculations were used to systematically analyze the electronic density of states (DOS) distribution of the five-element transition-metal-based high-entropy alloy. The results indicate that the d-orbital hybridization of the multiple principal transition metal elements forms a continuous stepped energy structure near the Fermi level. This electron distribution, regulated by the unique configurational entropy of the high-entropy alloy, significantly enhances the electron transition probability from the ultraviolet to the mid- and far-infrared, resulting in a high absorption rate exceeding 86% across the entire spectral range. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is the infrared absorption curve of the AlCrCuNiNb high entropy alloy coating prepared in Example 1; Figure 2 This is the visible light absorption curve of the AlCrCuNiNb high entropy alloy coating prepared in Example 1; Figure 3 Example 1: Distribution diagram of electronic state density of AlCrCuNiNb high entropy alloy prepared. DETAILED DESCRIPTION

[0020] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.

[0021] In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention may also be implemented in other ways different from those described herein. Those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0022] Secondly, the term "one embodiment" or "embodiment" herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The phrase "in one embodiment" appearing in various places throughout this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive of other embodiments.

[0023] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, methods, and instruments used are conventional in the art and can be obtained commercially by those skilled in the art unless otherwise specified.

[0024] Example 1: (1) Preparation of high entropy alloy powder: Five metal powders, aluminum (Al: 25 mol%), chromium (Cr: 20 mol%), copper (Cu: 15 mol%), nickel (Ni: 25 mol%), and niobium (Nb: 15 mol%), were selected and mixed in molar ratio and added into a high-energy ball mill. The ball-to-material ratio was set to 16:1. The milling was carried out at a speed of 450 rpm under argon protection for a total milling time of 60 h to obtain AlCrCuNiNb solid solution powder with a particle size of about 100 nm, which is the high entropy alloy powder.

[0025] (2) Substrate pretreatment: 6061 aluminum alloy substrate was selected and polished with 100-mesh diamond sandpaper to remove the oxide layer. The substrate was ultrasonically cleaned in ethanol and deionized water for 30 minutes, and then dried at 80°C for later use.

[0026] (3) Composite slurry preparation: High entropy alloy powder and polyurethane resin were mixed in a mass ratio of 1:2, stirred at 2000 rpm for 2 hours, and then ultrasonically treated for 30 minutes to eliminate agglomeration. Stirring was carried out at high speed in a blender to form a stable suspension slurry by utilizing the anchoring effect of the polyurethane molecular chain.

[0027] (4) Scraping: Set the scraper gap to 40 μm and apply the coating evenly on the pretreated aluminum substrate. Allow each layer to level for 20 minutes at room temperature. Apply three layers in total. Densification of the coating is achieved through a step-by-step curing process, ultimately obtaining a composite coating with controllable thickness.

[0028] (5) Curing treatment: Curing at room temperature for 24 hours to form a high entropy alloy-polyurethane cross-linked network structure, which is the high entropy alloy coating.

[0029] The infrared and visible light absorption properties of the AlCrCuNiNb high entropy alloy coating prepared in Example 1 were tested using a Fourier transform infrared spectrometer (FTIR, wavelength range 2-16 μm) and an ultraviolet-visible-near infrared spectrophotometer (UV-Vis-NIR, wavelength range 0.2-2.5 μm). Figure 1 and 2 As shown by Figure 1 and Figure 2 It can be seen that there are broadband absorption bands in all the above-mentioned bands. This is due to the stepped energy level structure formed by the hybridization of d orbitals of multiple transition metal elements, which in turn promotes electron transitions covering the entire band from ultraviolet to far infrared.

[0030] In order to verify the formation of a stepped energy structure by the hybridization of d orbitals of multiple transition metal elements, density functional theory (DFT) calculations were performed on the AlCrCuNiNb high entropy alloy system to obtain its electronic density of states (DOS). Specifically, the ATAT software was used to construct the supercell using the quasi-random special quasicrystal approximation (SQS) method, and the Vienna Ab Initio Simulation Package (VASP) software package was used for calculations. 450 eV was determined as the cutoff energy. During the structure optimization and self-consistent field (SCF) calculation process, the energy convergence criterion was set to less than 10 -5 eV, the force convergence criterion was set to less than 0.01eV / Å, and the Monkhorst-Pack method was used to sample the Brillouin zone with k-points, with a k-point grid of 3*3*3. After static self-consistency, the density of states (DOS) calculation was performed using a denser k-point grid of 13*13*13. The results are shown in the figure. Figure 3 As shown, Figure 3 The synergistic effect of the hybridization of d orbitals of Cr, Nb, Ni, and Cu with sp orbitals of Al on the full spectrum absorption is demonstrated.

[0031] The above description is merely a preferred embodiment of the present invention. Given that those skilled in the art can make appropriate changes and modifications to the above embodiments, the present invention is not limited to the specific embodiments described above. Some modifications and changes to the present invention should also fall within the scope of protection of the claims of the present invention.

Claims

1. A visible / infrared wide spectrum high absorption transition metal-based high entropy alloy material, characterized in that: The high entropy alloy comprises Al, Cr, Cu, Ni and Nb elements, and has a single-phase BCC solid solution structure.

2. The high entropy alloy material according to claim 1, characterized in that The molar percentage of each component is: Al: 5-35%, Cr: 5-35%, Cu: 5-35%, Ni: 5-35%, Nb: 5-35%.

3. The high entropy alloy material according to claim 1, characterized in that The molar percentage of each component is: Al: 25%, Cr: 20%, Cu: 15%, Ni: 25%, Nb: 15%.

4. A method for preparing the visible / infrared wide spectrum high absorption transition metal-based high entropy alloy material according to any one of claims 1 to 3, characterized in that: The metal particles constituting the high entropy alloy material are placed in a high-energy ball milling tank in a molar ratio and ball milled under argon protection to obtain the high entropy alloy material.

5. The preparation method according to claim 4, characterized in that The ball milling speed is 300-600rpm, the time is 20-100h, and the ball-to-material ratio is 10~20:

1.

6. A visible / infrared wide spectrum high absorption transition metal-based high entropy alloy coating, characterized in that: The invention comprises the visible / infrared wide spectrum high absorption transition metal-based high entropy alloy material according to any one of claims 1 to 3 and a polyurethane resin.

7. The high entropy alloy coating according to claim 6, characterized in that The mass ratio of the high entropy alloy material to the polyurethane resin is 1:(1~5).

8. The high entropy alloy coating according to claim 6, characterized in that The coating thickness is 20-100μm.

9. A method for preparing a visible / infrared wide spectrum high absorption transition metal-based high entropy alloy coating according to any one of claims 6 to 7, characterized in that: The high entropy alloy powder and the polyurethane resin are evenly mixed to obtain a composite slurry, and the composite slurry is evenly scraped on the pretreated substrate using a scraper, and multiple coatings are performed. After each coating, the slurry is leveled at room temperature. After the coating is completed, the slurry is allowed to stand and solidify at room temperature. After the curing is completed, a high entropy alloy coating is obtained.

10. Use of the visible / infrared wide spectrum high absorption transition metal-based high entropy alloy coating according to any one of claims 6 to 7, characterized in that: Used as an ultra-black coating to protect optical devices in deep space exploration missions.